MODERN LEGISLATION OF THE REPUBLIC OF UZBEKISTAN IN THE FIELD OF RELIGION - Ashurov N. B. (Web of Journals Publishing, 2024)
The article deals with the modern legislation of the Republic of Uzbekistan in the field of religion. The article analyzes the main legal documents aimed at preventing and combating the spread of the ideology of radical Islam in the region. The effectiveness of state legislation on religion in relation to existing extremist and terrorist threats in the region is assessed.
Keywords: Islam, extremism, terrorism, Uzbekistan, legislation, religion.